A Contextual Approach to Unconstitutional Constitutional Amendments: Judicial Power and the Basic Structure Doctrine in Malaysia. Issue 1 (July 2020) - NEO, Jaclyn L.
Abstract: This article takes a contextual approach to analyzing judicial engagement with the doctrine of unconstitutional constitutional amendments. It argues that in assessing judicial reception of the basic structure doctrine, and the content of the constitutional identity that such a doctrine seeks to preserve, a normative universalist or even functionalist approach is not sufficient. Instead, such a doctrine should be justified and understood contextually. It is necessary to contextualize constitutional identity in order to give it a robust character, rather than assuming a set of characteristics most often associated with liberal democratic constitutionalism and without understanding the political, social, and economic conditions in which the constitution operates. This article thus uses the example of Malaysia and how the courts have engaged with the basic structure doctrine to show how a contextual approach could have greater explanatory effect, including on why certain issues are more strongly contested in some countries than in others.